Construction of Biopond Houses to Increase BSF Maggot Production in the Context of Reducing Organic Waste in Medan - Hasibuan, Azhari; Hakim, Lukman; Nasution, Delima Lailan Sari (Talenta Publisher, 2022)
The Joint Business Group of Pondok Maggot Marelan which is located in the Village of Falls, District of Medan Marelan, Medan City is a business group that carries out the cultivation of Black Soldier Fly (BSF) which has been able to produce maggot larvae of about 60 kg per week. The existence of this group is very helpful for the community and the local government in managing the existing organic waste. The increase in the production of maggot larvae is hampered because the capacity of the maggot house is still too small. In addition, the processing of existing maggot larvae is also still limited, namely as chicken or duck feed. This service aims to assist partners in increasing and managing the production of existing maggot larvae. Making maggot houses and training in making floating fish feed using maggot larvae is also important as an alternative in post-harvest management of maggot larvae. This service output program includes fish feed training services, making BSF maggot houses with temperature and humidity sensors, activity videos, and scientific articles. BSF cultivation counseling and training activities have been carried out well. The conclusion of this activity is an increase in maggot production due to the addition of BSF maggot biopond houses. In addition, partners also gain new knowledge in the form of how to manage BSF maggots into floating fish feed that can be used in freshwater fish farming.